Eco-Efficiency Measures in The Leather Industry. An Educational Case - Gabriel Jinga; Madalina Dumitru; Elena-Mariana Glavan; Gabriel Radu (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- How can a company in the leather industry improve its eco-efficiency? Motivation- In the academic literature, there is a significant number of contributions that address the intersection between accounting and sustainability. However, the number of papers dedicated to education is rather limited. Management accounting is a domain which can broadly contribute to sustainability, as the professionals are collecting, interpreting, and presenting information on a regular basis. Idea- In this paper, we provide an educational case regarding a few eco-efficiency measures in the leather industry. Data- Data are collected from one of the biggest leather goods producers in Romania. Some of the figures were adjusted for confidentiality reasons. Tools- The material flow cost accounting methodology was used to explain the implementation of environmental management accounting in the case company. Contribution- The study improves the literature on educational cases that can be used in teaching environmental management accounting. The described case study is useful both in an online and offline environment.
Keywords: M41; 650; eco-efficiency; environmental management accounting; material flow cost accounting; case study; accounting education.